Simple and efficient custom transcription activator-like effector gene synthesis via twin primer assembly - Song Wang; Yan Yu; Yuhualei Pan; Huan Wang; Yushang Zhao; Mengyao Qu; Yanbing Zhu (BioTechniques)
Transcription activator-like effector (TALE) nucleases (TALENs) efficiently recognize and cleave DNA in a sequence-dependent manner. However, current TALE custom synthesis methods are either complicated or expensive. Here we report a simple and low-cost method for TALE construct assembly. This method utilizes the denaturation/reannealing nature of double-stranded DNA to create a unique single-stranded DNA overhang for proper ordering of TALE monomers in an engineered multimer. We successfully synthesized two TALEN pairs targeting the endogenous TET1 locus in human embryonic kidney cells and demonstrated their editing efficiency. Our method provides an alternative simple, low-cost method for effective TALEN assembly, which may improve the application of TALE-based technology.